Alfred Lord Tennyson's 'In Memoriam' : a reading guide - Barton, Anna, 1979- (Edinburgh University Press, 2012)
Introduces Tennyson's famous elegy to first-time readers, students and teachers of the poem. This guide takes readers through Tennyson's elegy, providing:. The full text of the poem Information about its cultural, historical and literary contexts Four different reading strategies for approaching the text Suggested seminar activities, assessments and module outlines for teachers and lecturers In Memoriam is one of the most famous and influential poems of the 19th century. Composed over nearly three decades and spanning over 100 sections, it is one of the longest elegies in the English language. It is at once a deeply personal description of grief and a wide-ranging discussion of its age.
Keywords: Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892. -- In memoriam.; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892 -- Criticism and interpretation.; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892; In memoriam (Tennyson, Alfred Tennyson, Baron); POETRY -- English, Irish, Scottish, Welsh.; POETRY -- General.; Criticism, interpretation, etc.